A Case Study of Church Growth by Church Planting in Germany: Are They Connected? - Paas, Stefan (International bulletin of mission research, 2018)
It is widely believed that the planting of new churches is a cause of church growth, regardless of culture or context. However, surprisingly little reliable and relevant data are presented to support this claim. In this article recent membership data of the Bund Freier evangelischer Gemeinden (Association of Free Evangelical Congregations) in Germany is explored to examine the relationship between church planting and church growth. The data show that there is indeed a positive correlation, but since there is also a clear correlation between rapid growth and decline, the evidence should be treated with care.